Effects of manganese on soybean growth in a Cerrado soil of Triângulo Mineiro, MG, Brazil - Junior, João Alberto de Oliveira; Malavolta, Eurípedes; Cabral, Cleusa Pereira (Pesquisa Agropecuaria Brasileira, 2000)
Manganese deficiency in soybean [Glycine max (L.) Merrill) and in other crops could be due to its low levels in the soil, or to its unavailability induced by liming. The objective of this research was to verify the soybean mineral composition in relation to Mn availability. An experiment was carried out in a greenhouse, using soil from Patrocínio, MG, Brazil, where the cultivated coffee shows symptoms of Mn deficiency. Mn was applied at the rates of zero, 10, 50 and 100 mg kg-1 with an additional treatment of 0.6% of foliar applied Mn and two rates of lime, namely: zero and 2.7 t ha-1. Mn concentration in the plant tissue was increased with the rate of lime application; liming, however, caused a Mn reduction. It must be pointed out that the lowest Mn level in the leaves was 84 mg kg-1, at the zero rate of Mn with lime. Mn ratio caused an increase both in dry matter and grain yield either in the presence and absence of lime. Liming did not induce any symptom of Mn deficiency in the leaves. Leaf applied Mn was efficient to raise and maintain soybean yield.
Keywords: liming; soil toxicity; nutrient transport; Glycine max; leaves